Reproducing women : medicine, metaphor, and childbirth in late imperial China - Wu, Yi-Li, 1965- (ACLS Humanities E-Book., 2010)
This innovative book uses the lens of cultural history to examine the development of medicine in Qing dynasty China. Focusing on the specialty of "medicine for women"(fuke), Yi-Li Wu explores the material and ideological issues associated with childbearing in the late imperial period. She draws on a rich array of medical writings that circulated in seventeenth- to nineteenth-century China to analyze the points of convergence and contention that shaped people's views of women's reproductive diseases. These points of contention touched on fundamental issues: How different were women's bodies fro.